Evaluation of probiotic yoghurt by the mixed culture with Lactobacillus plantarum A3 - Fengxuan Lang; Jianzhu Wen; Zhen Wu; Daodong Pan; Linjun Wang (Food Science and Human Wellness)
Lactic acid bacteria (LAB) fermentation is the simplest and safest way of food preservation, and the use of probiotics in yoghurt could provide dairy products with unique flavors, textures and health benefits. In this study, Lactobacillus bulgaricus, Streptococcus thermophilus, L. reuteri DSMZ 8533 and the potential probiotic strain L. plantarum A3 were used for the milk fermentation. Results found the texture properties such as hardness, consistency, and viscosity of the yoghurt were enhanced in the mixed culture condition. Furthermore, components like amino acid (leucine), vanilla (vanillin), C18:3n6 (unsaturated fatty acids) were also accumulated in L. plantarum A3 fermented yoghurt, which leads to the significant sensory profiling difference compared with the former plain yoghurt. All these results proved L. plantarum A3 is a potential probiotic strain which could enhance the sensory and nutrition profiling of the fermented milk. Future work still needs to be done on the synergistic interaction between the traditional strains and the probiotics during the fermentation process.